2020
DOI: 10.5999/aps.2020.00612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interventions and speech outcomes for individuals with submucous cleft palate

Abstract: Background This study aimed to identify the initial diagnostic characteristics and treatment status of children with submucous cleft palate (SMCP) and to examine the relationship between the timing of surgical correction and the degree of articulation and resonance improvement.Methods This retrospective study included 72 children diagnosed with SMCP between 2008 and 2016. The evaluation criteria were the age of the initial visit, total number of visits, age at the end of treatment, speech problems, resonance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
(68 reference statements)
2
11
0
Order By: Relevance
“…A group of Korean researchers reported a similar value, of which 37.5% had CA before primary surgery, which decreased to 19.2% after the surgical intervention and speech therapy, but it is not clear who received it. 31 When consulting the studies cited in this review in detail highlights the work of Baek et al, 33 who reported 45% of CA; Park et al, 34 who reported 40% glottal articulation and 13% palatalized articulation, and Ten Dam et al 5 with a 56% of articulation problems. On the other hand, in this retrospective study, no information was obtained regarding the patients who received speech therapy and for how long, so future investigations should take these factors into account.…”
Section: Discussionmentioning
confidence: 94%
“…A group of Korean researchers reported a similar value, of which 37.5% had CA before primary surgery, which decreased to 19.2% after the surgical intervention and speech therapy, but it is not clear who received it. 31 When consulting the studies cited in this review in detail highlights the work of Baek et al, 33 who reported 45% of CA; Park et al, 34 who reported 40% glottal articulation and 13% palatalized articulation, and Ten Dam et al 5 with a 56% of articulation problems. On the other hand, in this retrospective study, no information was obtained regarding the patients who received speech therapy and for how long, so future investigations should take these factors into account.…”
Section: Discussionmentioning
confidence: 94%
“…Swanson et al 18 assessed the timing of SMCP repair by Furlow palatoplasty, concluding that repair at or after 4 years is more likely to be associated with persistent misarticulation whereas treatment before 4 years is associated with reduced risk of borderline or incompetent speech. Jung et al 19 similarly highlight the importance of early diagnosis and intervention. They report this improves speech and reduces the likelihood of requiring secondary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They report this improves speech and reduces the likelihood of requiring secondary surgery. 19 The authors also concluded that delayed intervention is often due to delayed diagnosis; though anatomical abnormalities are identified they are unclear, causing diagnosis to rely on speech analysis later in life. Early assessment of SMCP cases by a MDT with SMCP scoring may reduce the incidence of such delays.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of preoperatively juvenile cleft palate patients. 30 32 Rhinomanometry which is considered the best modality for objective evaluation of nasal emission in cleft patients and is widely used in otorhinolaryngology in China. In the future, we will consider this instrument in the objective evaluation of nasality and nasal emission.…”
Section: Discussionmentioning
confidence: 99%